FAKTOR PENYEBAB KEJADIAN ANEMIA PADA REMAJA DITINJAU DARI ASPEK POLA MAKAN - Octovina Soumokil; Griselda Fortunata Susilo Putri; Dorce Sisfiani Sarimin; Patemah Patemah (Ensiklopedia Research and Community Service Review, 2026)
To date, the incidence of anemia in Indonesia remains one of the public health issues that requires serious and sustained attention. Adolescence is a period of rapid growth, during which iron requirements increase to support tissue growth, an increase in blood volume, and the development of reproductive organs. The purpose of this study was to identify the factors contributing to the incidence of anemia among adolescents from the perspective of dietary patterns. A cross-sectional study design was used in this research. The study was conducted at a high school in Banjarmasin. The sample consisted of 85 female students. Simple random sampling was used. A questionnaire was employed as the research instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between dietary patterns (p-value: 0.037) and sleep duration (p-value: 0.002) with the incidence of anemia in adolescent girls. It is recommended that school officials and local health workers conduct educational and awareness campaigns about anemia in adolescents, as well as provide regular health checkups and iron supplements.Keywords: Anemia, Sleep Duration, Eating Habits, Adolescents